2013
DOI: 10.3390/nu5041436
|View full text |Cite
|
Sign up to set email alerts
|

Short Term (14 Days) Consumption of Insoluble Wheat Bran Fibre-Containing Breakfast Cereals Improves Subjective Digestive Feelings, General Wellbeing and Bowel Function in a Dose Dependent Manner

Abstract: This study investigated whether increasing insoluble (predominantly wheat bran) fibre over 14 days improves subjective digestive feelings, general wellbeing and bowel function. A single centre, multi-site, open, within subjects design with a 14 day non-intervention (baseline) monitoring period followed by a 14 day fibre consumption (intervention) period was performed. 153 low fibre consumers (<15 g/day AOAC 985.29) completed a daily symptom diary for 14 days after which they consumed one bowl of ready-to-eat b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
2

Year Published

2014
2014
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 24 publications
1
22
0
2
Order By: Relevance
“…For instance, similar to Jenkins et al 11 we found an increase of 2.7 grams of FWW for each gram of supplemented dietary fibre. Moreover, we found an increase of 0.95 grams of FDW per day and an increase in stool frequency of 0.006 times per day for each gram of dietary fibre added to the diet, which is in line with data reported in the review of de Vries et al 2 For the effect of intact wheat fibre on stool consistency, previous results are inconsistent as some studies show that wheat fibre 'loosens stool', 13 whereas others report no significant effect. 14 The latter fits our results.…”
Section: Discussionsupporting
confidence: 91%
“…For instance, similar to Jenkins et al 11 we found an increase of 2.7 grams of FWW for each gram of supplemented dietary fibre. Moreover, we found an increase of 0.95 grams of FDW per day and an increase in stool frequency of 0.006 times per day for each gram of dietary fibre added to the diet, which is in line with data reported in the review of de Vries et al 2 For the effect of intact wheat fibre on stool consistency, previous results are inconsistent as some studies show that wheat fibre 'loosens stool', 13 whereas others report no significant effect. 14 The latter fits our results.…”
Section: Discussionsupporting
confidence: 91%
“…It is known that insoluble fibres such as inulin, bran and rye may cause more bloating and flatulence and sometimes this is a reason for discontinuation of treatment . In one study of wheat bran (insoluble fibre), bloating improved but flatulence worsened . Here, we found that approximately 50% of patients in the mixed fibre group reported improvement in bloating and this percentage was twofold higher than that seen in the psyllium group.…”
Section: Discussionmentioning
confidence: 46%
“…Smith et al [45] have also shown that habitual breakfast consumption is was associated with a lower prevalence with respect to the common cold. Lawton et al [46] previously reported that consumption of high fibre breakfast cereals may improve self-assessed digestive functionality and general wellbeing.…”
Section: Breakfast Eating Habits and Shsmentioning
confidence: 99%